(3GdLeY GdZQjH aj JQJjH Bj eZfj GddHjHs - (3CHhYHO Gddg eMeO Hf bGSe GdCfUGQj, GdQUGYs; (3GHf gTGe , YHO Gddg Hf jhSa Hf CMeO Hf YHO Gddg Hf jhSa, LeGd GdOjf , CHh eMeO,J (B761 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg, aEfj deG cfJ ehdYG HGdfXQ aj cJGH GdTjN GHf gTGe s
(3BNQgG (B:s
(3hEPG cGfJ GdeZGQHI eKHJI gPG GdTQjW de jPcQ dg LhGHkG hdG jUdM GdePchQ Cf jchf LhGHkG dg s
(3GdfSNI HgG MhGTs
(3HHYV ChQGbgG JbWjYs
(3JHUQI GdYfhGf (B:s
(3JQJjHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B147 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B163 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B465s
Keywords: (3GdfMhs